A matched model-based synthetic aperture focusing technique for acoustic microscopy - Wüst, Michael; Schwarz, Michael; Eisenhart, Johannes; Nierla, Michael; Rupitsch, Stefan (Ndt & E International, 2019)
This contribution deals with an advanced synthetic aperture focusing technique for acoustic microscopy, which enables an almost precise reconstruction of the reflectivity distribution of both fluid-like and solid specimen. The presented approach is designed for single-element ultrasonic immersion transducers as they are commonly used in scanning acoustic microscopes. In practice, the resulting images offer at least lateral and axial resolutions of a focused image, which was acquired by a transducer with double center frequency. Moreover, the results show very low side lobe levels and the approach reconstructs the shape of inner defects even in images with present multiple reflections. A comparison with the well-known delay-and-sum technique reveals that the introduced approach offers a significantly more precise reconstruction of the given reflectivity distribution, especially when a complex reflectivity distribution is investigated. The advanced synthetic aperture focusing technique is applied to a generic test samples and to a curved multi-layered compound specimen.
CRIS-Team Scopus Importer:2019-05-03
Keywords: 2010 MSC: 00–01; 99–00; Acoustic microscopy; Numerical simulation; Smart material compounds; Synthetic aperture focusing techniques; Ultrasonic imaging

A model-based synthetic aperture focusing technique for acoustic microscopy - Wüst, Michael; Nierla, Michael; Rupitsch, Stefan (Ultrasonics Symposium (IUS), 2016 IEEE International, 2016)
This contribution is concerned with a technique to precisely measure the physical dimensions of flaws in solid specimen by pulse-echo mode acoustic microscopy. We have implemented a synthetic aperture focusing technique (SAFT), which is based on a semi-numerical simulation approach (SIRFEM). In acoustic microscopy, one normally applies single-element transducers with center frequencies above 10MHz. Due to the very short wavelengths, numerical simulations demand a very fine discretized measurement setup. This would lead to extensive calculation costs. Therefore, we model the sound propagation in the fluid coupling medium between transducer surface and specimen analytically by the spatial impulse response (SIR) method. Only the mechanical wave propagation in the solid specimen is then simulated by a higher-order finite element method (FEM). This coupled SIRFEM method can be used to calculate the RF signal output (i.e., echo data) of ultrasonic transducers. The presented model-based SAFT algorithm is based on an optimized filter-kernel, which is generated by an adapted SIRFEM simulation.
Keywords: ultrasound; non-destructive evaluation; numerical simulation; synthetic aperture focusing techniques

Comparison of different vector Preisach models for the simulation of ferromagnetic materials - Nierla, Michael; Löffler, Michael; Kaltenbacher, Manfred; Rupitsch, Stefan (Abstracts of the 18th International IGTE Symposium on Numerical Field Calculation in Electrical Engineering IGTE 2018, 2018)
The Mayergoyz vector Preisach model is oftentimes used for the simulation of hysteresis phenomena of both isotropic and anisotropic ferromagnetic materials. However, the derivation of the required Preisach weights as well as the efforts to resolve the full 2D/3D space may lead to rather high computational costs. For isotropic materials, two other vector Preisach models developed by Sutor might offer a light-weight alternative. In this contribution, we compare three different vector Preisach models with respect to their representation of measured data and their computational costs.<br
Keywords: Hysteresis Modeling; Vector Preisach Model

Comparison of different vector Preisach models for the simulation of ferromagnetic materials - Nierla, Michael; Löffler, Michael; Kaltenbacher, Manfred; Rupitsch, Stefan (Compel-The International Journal For Computation and Mathematics in Electrical and Electronic Engineering, 2019)
Purpose The numerical computation of magnetization processes in moving and rotating assemblies requires the usage of vector hysteresis models. A commonly used model is the so-called Mayergoyz vector Preisach model, which applies the scalar Preisach model into multiple angles of the halfspace. The usage of several scalar models, which are optionally weighted differently, enables the description of isotropic as well as anisotropic materials. The flexibility is achieved, however, at the cost of multiple scalar model evaluations. For solely isotropic materials, two vector Preisach models, based on an extra rotational operator, might offer a lightweight alternative in terms of evaluation cost. The study aims at comparing the three mentioned models with respect to computational efficiency and practical applicability. Design/methodology/approach The three mentioned vector Preisach models are compared with respect to their computational costs and their representation of magnetic polarization curves measured by a vector vibrating sample magnetometer. Findings The results prove the applicability of all three models to practical scenarios and show the higher efficiency of the vector models based on rotational operators in terms of computational time. Originality/value Although the two vector Preisach models, based on an extra rotational operator, have been proposed in 2012 and 2015, their practical application and inversion has not been tested yet. This paper not only shows the usability of these particular vector Preisach models but also proves the efficiency of a special stageless evaluation approach that was proposed in a former contribution.
Keywords: Magnetic hysteresis; Everett function; Vector Preisach model; Material modelling; Computational electromagnetics; Vector vibrating sample magnetometer; Vector hysteresis

Computation of rotational hysteresis losses by vector Preisach models based on rotational operators - Nierla, Michael; Kaltenbacher, Manfred; Rupitsch, Stefan (Abstracts of the 19th International IGTE Symposium on Numerical Field Calculation in Electrical Engineering IGTE 2020, 2020)
The vector Preisach model by Mayergoyz well predicts rotating hysteresis losses at low amplitudes of the applied field. However, in its original form, it fails to predict the reduction of such losses at high fields. In recent years, two variants of a novel vector Preisach model based on rotational operators have been published and investigated with respect to general accuracy and performance. The aim of this contribution is to examine the capabilities of the named vector Preisach models in terms of rotational hysteresis loss calculation
Keywords: Hysteresis Modeling; Vector Preisach Model; Rotational Hysteresis Losses

Computation of rotational hysteresis losses by vector Preisach models based on rotational operators - Nierla, Michael; Kaltenbacher, Manfred; Rupitsch, Stefan Johann (Compel-The International Journal For Computation and Mathematics in Electrical and Electronic Engineering, 2022)
Purpose A major purpose of vector hysteresis models lies in the prediction of power losses under rotating magnetic fields. The well-known vector Preisach model by Mayergoyz has been shown to well predict such power losses at low amplitudes of the applied field. However, in its original form, it fails to predict the reduction of rotational power losses at high fields. In recent years, two variants of a novel vector Preisach model based on rotational operators have been published and investigated with respect to general accuracy and performance. This paper aims to examine the capabilities of the named vector Preisach models in terms of rotational hysteresis loss calculations. Design/methodology/approach In a first step, both variants of the novel rotational operator-based vector Preisach model are tested with respect to their overall capability to prescribe rotational hysteresis losses. Hereby, the direct influence of the model-specific parameters onto the computable losses is investigated. Afterward, it is researched whether there exists an optimized set of parameters for these models that allows the matching of measured rotational hysteresis losses. Findings The theoretical investigations on the influence of the model-specific parameters onto the computable rotational hysteresis losses showed that such losses can be predicted in general and that a variation of these parameters allows to adapt the simulated loss curves in both shape and amplitude. Furthermore, an optimized parameter set for the prediction of the named losses could be retrieved by direct matching of simulated and measured loss curves. Originality/value Even though the practical applicability and the efficiency of the novel vector Preisach model based on rotational operators has been proven in previous publications, its capabilities to predict rotational hysteresis losses has not been researched so far. This publication does not only show the general possibility to compute such losses with help of the named vector Preisach models but also in addition provides a routine to derive an optimized parameter set, which allows an accurate modeling of actually measured loss curves.
CRIS-Team WoS Importer:2022-02-18

Efficient numerical simulation of transducer outputs for acoustic microscopes - Rupitsch, Stefan; Nierla, Michael (13th IEEE SENSORS Conference, SENSORS 2014, 2014)
A semi-numerical simulation approach, the so-called SIRFEM is presented. This approach can be applied to efficiently predict transient output signals of ultrasonic imaging systems operating in pulse-echo mode. In particular, we concentrate on acoustic microscopes, which exploit ultrasound waves with center frequencies >10 MHz to visualize inner structures of solid specimens. While the ultrasound pulses between ultrasonic transducer and specimen surface are analytically modeled (spatial impulse response), we perform finite element simulations to describe wave propagation in the specimen. As the computed B-mode images for a plastic sample containing various inclusions (e.g., air) demonstrate, SIRFEM provides reliable transducer outputs. This implies that both, reflections at inner structures and multiple reflections between specimen surface and those structures are considered.

FEM-based optimization of an inverse-magnetostrictive pressure sensor - Löffler, Michael; Nierla, Michael; Kadur, Madlen; Sutor, Alexander; Lerch, Reinhard (Abstract Book, 2016)
The global demand for MEMS pressure sensors is constantly increasing. Usually, the piezoresistive or the capacitive effect is exploited in such devices. However, it has already been shown that sensors based on the inverse-magnetostrictive (Villari) effect feature a remarkable sensitivity while overcoming drawbacks of the established principles like temperature-instability and non-linearity. Although simulations are crucial for the further development and optimization, simulations incorporating the magnetostrictive and the inverse-magnetostrictive effect in such devices have been missing until now. In this contribution, we present an iterative FE-scheme using VSM- measurements to consider the stress-dependent permeability of the magnetostrictive layers of such sensors. With this approach, the dimensions of the single layers are optimized to achieve maximum sensitivity.
Keywords: Magnetostriction; inverse-magnetostrictive effect; Finite Element simulation; MEMS pressure sensor

Hybrid Semi-numerical Simulation Scheme to Predict Transducer Outputs of Acoustic Microscopes - Nierla, Michael; Rupitsch, Stefan (IEEE Transactions on Ultrasonics Ferroelectrics and Frequency Control, 2016)
We present a semi-numerical simulation method called SIRFEM, which enables the efficient prediction of high frequency transducer outputs. In particular, this is important for acoustic microscopy where the specimen under investigation is immersed in a coupling fluid. Conventional Finite Element (FE) simulations for such applications would consume too much computational power due to the required spatial and temporal discretization, especially for the coupling fluid between ultrasonic transducer and specimen. However, FE simulations are in most cases essential to consider the mode conversion at and inside the solid specimen as well as the wave propagation in its interior. SIRFEM reduces the computational effort of pure FE simulations by treating only the solid specimen and a small part of the fluid layer with FE. The propagation in the coupling fluid from transducer to specimen and back is processed by the so-called spatial impulse response (SIR). Through this hybrid approach, the number of elements as well as the number of time steps for the FE simulation can be reduced significantly, as it is presented for an axis-symmetric setup. Three B-mode images of a plane 2-D setup — computed at a transducer center frequency of 20 MHz — show that SIRFEM is, furthermore, able to predict reflections at inner structures as well as multiple reflections between those structures and the specimen’s surface. For the purpose of a pure 2-D setup, the spatial impulse response of a curved-line transducer is derived and compared to the response function of a cylindrically focused aperture of negligible extend in the third spatial dimension.
Keywords: Spatial Impulse Response; Finite Element Method; Pulse-Echo; Ultrasound; Microscopic Imaging

Iterative finite element scheme for magnetoelectric energy harvesters - Nierla, Michael; Löffler, Michael; Rupitsch, Stefan (Procedia Engineering - Eurosensors 2015, 2015)
Magnetoelectric (ME) energy harvesting devices consisting of layered magnetostrictive/piezoelectric composites exploit the large mechanical strains arising from movements inside an external magnetic field to increase the electrical power output of the piezoelectric layers. Numerical methods help to optimize the design and the efficiency of such setups. Methods based on the solution of one directly coupled equation system, however, can in general not account for the change in geometry which occurs due to the harvester's movement inside the external magnetic field. In this contribution, we present an iteratively coupled Finite Element (FE) scheme for such devices that does not only enable the coupled simulation of magnetostrictive and piezoelectric effects, but furthermore allows the consideration of changing geometrie
Keywords: Energy Harvesting; Magnetostriction; Piezoelectricity; Finite Element Method; Iterative Coupling

Modellgestützte Ultraschallmikroskopie zur dimensionellen Erfassung von Fehlstellen in Festkörpern - Wüst, Michael; Nierla, Michael; Rupitsch, Stefan (Fortschritte der Akustik, 2015)
Synthetische Aperturfokussierungstechniken (SAFT) werden bei ultraschallbasierten bildgebenden Messverfahren zur Verbesserung der Ortsauflösung im Bild eingesetzt. Zumeist berücksichtigen übliche SAFT-Algorithmen aber nicht den inneren Aufbau des untersuchten Prüflings. Im Folgenden wird ein Verfahren zur Ultraschallmikroskopie vorgestellt, das einen angepassten SAFT-Algorithmus zur Bildrekonstruktion nutzt. Das Verfahren wird zur zerstörungsfreien Werkstoffprüfung herangezogen. Es dient der Detektion und dimensionellen Erfassung von Fehlstellen innerhalb des Prüflings (z. B. Delaminationen in heterogenen Werkstoffverbunden). Dabei ist die Soll-Geometrie des untersuchten Prüflings a priori bekannt. Unter Nutzung dieser Vorkenntnisse können die Messsignale simuliert werden, die bei einer fehlerfreien Geometrie resultieren würden. Aus den erzeugten Daten wird ein räumlicher Filterkern modelliert, der die Grundlage des SAFT- Algorithmus bildet. Die Simulation mittels Finiter-Elemente- Methode (FEM) ist allerdings außerordentlich rechenintensiv und daher nicht praktikabel. Eine Reduzierung des Aufwands kann aber erreicht werden, indem eine analytische Berechnung des transienten Schallfeldes im Koppelmedium (Wasser) zwischen Ultraschall-Prüfkopf und Prüfling erfolgt. Hierfür kann die sogenannte ortsabhängige Impulsantwort (engl. ”Spatial Impulse Response”, kurz SIR) herangezogen werden. Für die Simulation der Schallausbreitung im Prüfling wird die FEM mit Ansatzfunktionen höherer Ordnung implementiert. Dieses hybride Simulationsverfahren wird als ”SIRFEM” bezeichnet. Das dadurch verbesserte Ortsauflösungsvermögen wird anhand erster Ergebnisse am Beispiel geometrisch simpler Prüflinge aufgezeigt.
Keywords: Ultraschall; Mikroskopie; zerstörungsfreie Prüfung

Nested-list Approach for the Stageless Evaluation of a Vector Preisach Model based on Rotational Operators - Nierla, Michael; Rupitsch, Stefan; Kaltenbacher, Manfred (AMA Conferences 2017 – SENSOR 2017 and IRS2 2017, 2017)
The Everett function is a widely used tool to evaluate the output of scalar Preisach hysteresis operators. Compared to a matrix-based implementation, the Everett function does not only allow a stageless evaluation of the switching state but, furthermore, reduces the required storage to a single list of dominant input minima and maxima. To deal with magnetic fields that change direction over time, a vector extension of the scalar Preisach model based on rotational operators can be utilized. This straight-forward extension enables an efficient description of vector hysteresis phenomena. Due to the dependency between the newly added rotational operator and the original switching operator, neither the usage of a single list nor the direct application of the Everett function is possible. In this contribution, we propose a nested-list data structure for the vector Preisach model based on rotational operators. Exploiting this data structure allows the usage of an adapted Everett function and, thus, an efficient, stageless representation of both the rotational operator as well as the switching operator.
Keywords: Everett Function; Hysteresis Modeling; Vector Preisach

Optimizing the dimensions of an inverse magnetostrictive MEMS pressure sensor by means of an iterative Finite Element scheme - Löffler, Michael; Nierla, Michael; Kadur, Madlen; Hoffmann, Marcel; Sutor, Alexander; Lerch, Reinhard (IEEE Transactions on Magnetics, 2016)
This paper proposes an iterative Finite Element (FE) scheme that accounts for the inverse magnetostrictive (Villari) effect. To do so, the permeability of magnetostrictive materials is updated according to the internal mechanical stress of the material at the end of each iteration step until convergence is reached. VSM measurements of prestressed thin-film samples are used to evaluate the stress-dependent permeability. Using the implemented scheme, it is possible to optimize the dimensions of inverse magnetostrictive microelectromechanical (MEMS) pressure sensors with a view to maximum sensitivity. Such sensors feature a sandwich-like structure with a planar coil embedded between two magnetostrictive layers. To date, only insufficient simulation results regarding the optimization of such devices have been published. We present results of simulations incorporating the inverse magnetostrictive effect that show the influence of the dimensions of single layers on the overall sensitivity.
Keywords: Magnetostriction; Inverse-Magnetostrictive Effect; Finite Element Simulation; MEMS Pressure Sensor

Stageless evaluation for a vector Preisach model based on rotational operators - Nierla, Michael; Sutor, Alexander; Rupitsch, Stefan; Kaltenbacher, Manfred (Compel-The International Journal For Computation and Mathematics in Electrical and Electronic Engineering, 2017)
Purpose – This paper aims to present a novel stageless evaluation scheme for a vector Preisach model that exploits rotational operators for the description of vector hysteresis. It is meant to resolve the discretizational errors that arise during the application of the standard matrix-based implementation of Preisach-based models. Design/methodology/approach – The newly developed evaluation uses a nested-list data structure. Together with an adapted form of the Everett function, it allows to represent both the additional rotational operator and the switching operator of the standard scalar Preisach model in a stageless fashion, i.e. without introducing discretization errors. Additionally, presented updating and simplification rules ensure the computational efficiency of the scheme. Findings – A comparison between the stageless evaluation scheme and the commonly used matrix approach reveals not only an improvement in accuracy up to machine precision but, furthermore, a reduction of computational resources. Research limitations/implications – The presented evaluation scheme is especially designed for a vector Preisach model, which is based on an additional rotational operator. A direct application to other vector Preisach models that do not rely on rotational operators is not intended. Nevertheless, the presented methodology allows an easy adaption to similar vector Preisach schemes that use modified setting rules for the rotational operator and/or the switching operator. Originality/value – Prior to this contribution, the vector Preisach model based on rotational operators could only be evaluated using a matrix-based approach that works with discretized forms of rotational and switching operator. The presented evaluation scheme offers reduced computational cost at much higher accuracy. Therefore, it is of great interest for all users of the mentioned or similar vector Preisach models.
Keywords: Everett function; Vector hysteresis; Vector Preisach model

Stageless evaluation scheme for a vector Preisach model based on rotational operators - Nierla, Michael; Sutor, Alexander; Rupitsch, Stefan; Kaltenbacher, Manfred (Proceedings of the 17th International IGTE Symposium on Numerical Field Calculation in Electrical Engineering IGTE 2016, 2016)
Scalar Preisach models often exploit the so-called Everett function to determine the output of the hysteresis operator. Thereby, the switching state of the Preisach plane is not stored directly in form of discrete matrix entries. Instead, a list of dominant input maxima and minima is saved, which can be utilized to recreate the actual switching state. This allows a stageless, i.e. continuous, representation of the output. The extension of the scalar model towards a vector model using rotational operators prohibits the direct use of the Everett function as the switching state can no longer be reconstructed from a single list of maxima and minima. In our contribution, we present a stageless evaluation scheme for the vector Preisach model based on rotational operators that takes nested lists to exactly represent both the state of the rotational operator as well as the switching state.
Keywords: Everett Function; Hysteresis Modeling; Vector Preisach Model

Stageless Evaluation Scheme for a Vector Preisach Model Based on Rotational Operators - Nierla, Michael; Sutor, Alexander; Rupitsch, Stefan; Kaltenbacher, Manfred (2nd Seminar on Ferroic Functional Materials and 12th International Workshop on Direct and Inverse Problems in Piezoelectricity, 2016)

Towards a model-based high-resolution ultrasonic measurement system for non-destructive testing - Wüst, Michael; Nierla, Michael; Rupitsch, Stefan (5th Scientific Symposium Proceedings, 2015)
This paper is concerned with a technique to measure the geometric dimensions of flaws in a multi-layered structure by using an ultrasonic system for non-destructive testing (NDT). In order to achieve appropriate spatial resolution, an acoustic microscope working with a synthetic aperture focusing technique (SAFT) has to be established. However, standard SAFT algorithms are not matched with the individual geometry of the solid specimen perfectly. Therefore, a custom spatial filter kernel needs to be generated instead. For this purpose, we apply a semi-numerical approach, the so-called SIRFEM. Thereby, sound propagation in fluid coupling media is modeled by using the spatial impulse response (SIR). Against that mechanical waves within the solid specimen are simulated by a higher-order finite element method (FEM). We utilize SAFT with the custom spatial filter kernel to investigate a homogeneous sample containing a flaw as well as to a multi-layered one. An estimation of the obtained spatial resolution will be given and the imaging results will be compared with those of the standard B-mode.
Keywords: ultrasound; acoustic microscopy; nondestructive evaluation; numerical simulation; SIRFEM